Operational and organisational stress among police officers in Johor during the COVID-19 pandemic - Zainal Abidin, Emilia; Mohamed, Noradila; Rasdi, Irniza; Mohamed, Noradila; Ismail, Ziity Sarah (Persatuan Pakar Perubatan Kesihatan Awam Malaysia,Malaysian Public Health Physicians Association, 2024)
Police officers are subjected to a higher risk of operational and organisational stress due to their duty, especially during the COVID-19 pandemic. This study aimed to establish the stress levels (low, moderate, and high cut-off values) using the Malaysian version of the police operational stress questionnaire (PSQ-Op) and the police organisational stress questionnaire (PSQ-Org). The study specifically sought to determine the operational and organisational stress levels among police officers in Johor during the COVID-19 pandemic. The Bahasa Malaysia version of PSQ-Op and PSQ-Org was distributed to 233 police officers in Johor. The cut-off values for the low, moderate, and high stress were established using the sample’s mean, while the sample’s tertile was to provide stress levels among those police officers. The low, moderate, and high stress for operational stress using the sample’s mean was found to be at 32.6 per cent, 27.5 per cent and 39.9, respectively, but were slightly higher (34.8%, 32.6% and 32.6%, respectively) when using the sample’s tertile. The low, moderate, and high operational stress was 23.6 per cent, 37.3 per cent, and 39.1 per cent, respectively, when applying the sample. Meanwhile, when using the sample’s tertile, the low, moderate, and high stress of organisational stress were 38.2 per cent, 30.9 per cent and 30.9 per cent, respectively. In conclusion, this study has found that the COVID-19 pandemic triggered higher levels of stress among police officers in Johor, calling for measures to be planned and implemented to avoid higher stress levels from affecting the effectiveness and productivity of police officers, which is crucial in maintaining public safety in Malaysia. Future studies need to focus on the other consequences of stress exposure by considering existing control measures.